Eksistensi Virtual, Identitas Nyata dalam Mengemukakan Pendapat di Media Sosial dan Aspek Hukum sebagai Sarana Aktualisasi Gen Z - Sri Ayu Irawati; Muh. Irfan Mukhlishin (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2025)
Expressing opinions is an aspect of communication that is not only a means of conveying ideas but also a fundamental mechanism for self-actualization. Social media has become a primary means for Generation Z (Gen Z) to express their opinions as a form of self-actualization. However, this freedom of expression often faces legal restrictions, social norms, and potential negative impacts. This study aims to analyze the context of Gen Z expressing opinions through social media as a form of self-actualization, as well as reviewing its legal aspects, driving factors, impacts, and applicable solutions. This article explores how expressing opinions becomes a means of fulfilling basic psychological needs in contemporary social dynamics. Based on literature analysis and recent studies, this paper combines communication theory, basic needs psychology, and self-actualization with considerations of social norms, culture, and power structures. The findings indicate that expressing opinions is strongly influenced by conditions for fulfilling basic needs (psychological safety, esteem, relationships) and by social dynamics; and that communication through expressing opinions can be at the core of the most fundamental self-actualization. This article provides a conceptual framework that can be tested empirically in local research, and has practical implications for education, organizations, and public policy.